2011
DOI: 10.2215/cjn.00410111
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Viral Negativity After Interferon for Chronic Hepatitis C Virus Infection in Hemodialysis

Abstract: SummaryBackground and objectives Interferon (IFN) and pegylated-IFN treatment of hepatitis C virus (HCV) infection in hemodialysis patients result in sustained virological response (SVR) rates of 45% and 37%, respectively. Although most nonhemodialysis patients who achieve SVR remain persistently viral negative, the durability of SVR in hemodialysis patients is unknown. We analyzed the rate of long-term virological negativity in hemodialysis patients who achieved SVR after IFN or pegylated-IFN through analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…The likelihood of remaining HCV RNAnegative for 48 months following antiviral treatment has been reported to be 86% for patients on haemodialysis and 95% after transplantation. 38,39 A minority of patients with HCV infection who are on dialysis receive antiviral treatment. Data from the Dialysis Outcomes and Practice Patterns Study showed that only ~1.0% of 4,589 patients with HCV infection received antiviral medication.…”
Section: Management and Treatment Of Patients With Hcvmentioning
confidence: 99%
“…The likelihood of remaining HCV RNAnegative for 48 months following antiviral treatment has been reported to be 86% for patients on haemodialysis and 95% after transplantation. 38,39 A minority of patients with HCV infection who are on dialysis receive antiviral treatment. Data from the Dialysis Outcomes and Practice Patterns Study showed that only ~1.0% of 4,589 patients with HCV infection received antiviral medication.…”
Section: Management and Treatment Of Patients With Hcvmentioning
confidence: 99%
“…Although haemodialysis patients with HCV infection who receive renal transplantation have survival advantages over those who remain on maintenance dialysis, these patients still have poor patient and graft survival, as well as have poor responses to interferon (IFN)-based therapy 7–9. In contrast, haemodialysis patients who eradicate HCV infection have improved clinical outcomes, whether they remain on maintenance dialysis or have had renal transplantation 10 11…”
Section: Introductionmentioning
confidence: 99%
“…Several of these specific scenarios are reviewed below and in Table . Importantly, these recommendations can be made because clearance of HCV in treated patients on the waitlist is durable after transplantation …”
Section: Scenarios In Which Treatment Before Transplantation Is Prefementioning
confidence: 99%